Preparación técnica en el fútbol y los adolescentes - Sanmartin Cruz, Hamilto Daniel (2015)
A good technical preparation footballers improves the skills prior to performance. Analyzing these conditions is that the problem arises, how it influences the technical preparation in sports performance males football team, college senior high school Fiscomisional Daniel Alvarez Burneo, period 2013-2014, in order to assess whether levels of preparation planned for college football players baccalaureate Fiscomisional Daniel Alvarez Burneo, period 2013-2014, at the stage of pre-skills training, technical are adequate; with the methodology was action research, the analysis-synthesis methods, inductive-deductive, historical and logical, comparison and diagnostic tests, a qualitative and quantitative approach, the survey allowed the diagnosis of the existing problem, the institution does not provides the necessary support, the two hours of training say they are partly right because it takes time for the few resources and means to possess the same way that triggers that can not be working properly the basics technical preparation and under these circumstances builds a proposal to solve these problems, with assessment test was observed in conditions in which young were the work of technical preparation was applied for 12 weeks to reassess the results taking in response improved fundamentals of technical preparation in football. Concluding that a good training schedule, allowing feeding, resting and training, adequate performance was achieved. Taking into account the resources and basic means by which it is told, was planned and performed an active and differentiated work, creating training effectiveness. Teaching in real game situations technical fundamentals were reflected in competition and working long enough, muscle fatigue is avoided, learning is enabled and improved the group's relationship. Recommending that the training schedule of a football team, it must plan beyond simple physiological reasons, ie should be subject to the planning of sports training and to develop adequate planning, resources must be considered and means by which counts. Both individual and collective technical foundations must be taught in real game situations and learning will be reflected in the competition, also work long enough, prevents muscle fatigue, enables learning and improves the group.